Effect of ellagic acid on BDNF/PI3K/AKT-mediated signaling pathways in mouse models of depression - Aslı Bedel; Coskun Usta (Iranian Journal of Basic Medical Sciences)
Objective(s): The aim of this study is to investigate the possible role of the hippocampal BDNF-PI3K-AKT signaling pathway in the antidepressant-like activity of ellagic acid (EA) in mice.Materials and Methods: Male BALB/C mice were divided into 5 groups; vehicle (0.1 ml/day), sertraline (5mg/kg), EA (1 mg/kg), EA+BKM120 (PI3K inhibitor), EA+MK2206 (AKT inhibitor). EA, sertraline and vehicle were injected intraperitoneally for 14 days. Locomotor activity was determined by open field test. The tail suspension test was used to detect the antidepressant-like effect. After behavioral tests, hippocampal tissue was obtained and Western blot analyzes were performed for BDNF and pAKT1. Results: Sertraline and EA provided a reduction in immobility time in the tail suspension test when compared with the control group. BKM120 and MK2206 administration reversed this effect of EA. No statistical difference was found between groups in terms of locomotor activity. EA treatment caused an increase in hippocampal BDNF and pAKT1 levels in mice. While inhibitory agent administrations did not affect the increase of BDNF induced by EA, MK2206 administration reversed the increase in pAKT1 observed with EA.Conclusion: It has shown that EA has an antidepressant-like effect in mice without changing locomotor activity, and this effect may be mediated by the BDNF-PI3K-AKT signaling pathway.